Recent progress in cassava agronomy research in the Philippines - Evangelio, Fernando A.; Villamayor, F.G.; Dingal, A.G.; Ladera, Julieta C.; Medellin, A.C.; Miranda, J.; Sajise, G.E. (International Center for Tropical Agriculture, 1995)
In Leyte, the long-term fertility trial under coconut showed significant responses to fertilizers after the second cropping cycle. Highest yields were obtained in treatments with 90 kg/ha of P O and 60 kg/ha of N and K O, while lowest yields were obtained in treatments without P application. In another trial there was a significant interaction between time-of planting and age-at-harvest. When intercropping maize within cassava rows, the yield of cassava was not reduced if the fertilizer requirements of both crops were met and the population of maize was only half of that of the monocrop. In an erosion control trial, large soil losses were observed in plots where vetiver or lemon grass had been planted as contour barriers, especially during the first year of establishment. Application of grass mulch continued to be the most effective treatment in reducing erosion, while it also resulted in the highest yield. During the fifth cropping cycle, it was observed that plots with complete fertilizer (60-60-60 kg/ha) application had the highest soil loss, while plots with grass mulch had again the lowest. Root yields were highest with the application of mulch and lowest in plots with lemon and vetiver grass barriers. In Bohol, significant differences in yield due to fertilizer levels were observed in the second, third and fourth cropping cycles. The main response was to K and N application. No significant differences in yield were observed between the two cultivars. Stake length significantly affected the root yield of cassava in the first and second year, but not in the third year of cropping. A significant interaction was observed among stake length, position of planting and cultivar. In an intercropping trial, cassava yields were not significantly affected by interplanting of either soybean, mungbean, cowpea, peanut or pole sitao. However, cassava row spacing significantly affected the yields of cassava and intercrops. In Negros Occidental the long-term fertility trial showed a significant yield response only to the application of N. There were significant differences among the two cultivars, but no significant interaction between fertilizer and cultivar. Crop residue incorporation or removal had still no significant effect on yield during the 3rd cropping cycle. An intercropping trial showed that cassava yields were significantly reduced by intercropping with all crops except soybean in the second and third year. Alley cropping with Leucaena leucocephala, Gliriddia sepium or Crotalaria sp markedly reduced cassava yields.